Updated National and International Hypertension Guidelines: A Review of Current Recommendations - Kjeldsen, Sverre (Drugs, 2014)
Despite the availability of effective pharmacological treatments to aid the control of blood pressure, the global rate of uncontrolled blood pressure remains high. As such, further measures are required to improve blood pressure control. Recently, several national and international guidelines for the management of hypertension have been published. These aim to provide easily accessible information for healthcare professionals and patients to aid the diagnosis and treatment of hypertension. In this review, we have compared new and current guidelines from the American and International Societies of Hypertension; the American Heart Association, American College of Cardiology and the US Center for Disease Control and Prevention; the panel appointed to the Eighth Joint National Committee; the European Societies of Hypertension and Cardiology; the French Society of Hypertension; the Canadian Hypertension Education Program; the National Institute for Health and Clinical Excellence (UK); the Taiwan Society of Cardiology and the Chinese Hypertension League. We have identified consensus opinion regarding best practises for the management of hypertension and have highlighted any discrepancies between the recommendations. In general there is good agreement between the guidelines, however, in some areas, such as target blood pressure ranges for the elderly, further trials are required to provide sufficient high-quality evidence to form the basis of recommendations.